1980
DOI: 10.1002/hlca.19800630846
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of cannabinoids. Part 3: Major metabolites of (3R, 4R)‐Δ1‐tetrahydrocannabinol

Abstract: The metabolic transformations of the psychotropic cannabinoid (3R, 4R)-A1tetrahydrocannabinol (5) (= A'-THC) by cultures of Fusarium nivale, Gibberella fujikuroi (both Ascomycetes) and Thamnidium elegans (Phycomycetes) were investigated. A number of metabolites, 1-4 and 6-9 were isolated from the incubations, partly purified and their structures elucidated by combined gas chromatography/mass spectrometry. Four of these metabolites, 1"-hydroxy-A'-THC (4), 2"-hydroxy-A1-THC (l), 6B-hydroxy-A'-THC (8) and 2", 6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Biotransformation of cannabinoids to glucosylated forms by plant tissues (Tanaka et al 1997) and various oxidized derivatives by microorganisms (Robertson et al 1978;Binder and Popp 1980) have been reported; as well as biotransformations for olivetol (McClanahan and Robertson 1984). However, the best studied biotransformations are in animals and humans (Mechoulam 1970;Watanabe et al 2007).…”
Section: Cannabinoid Biosynthesismentioning
confidence: 97%
“…Biotransformation of cannabinoids to glucosylated forms by plant tissues (Tanaka et al 1997) and various oxidized derivatives by microorganisms (Robertson et al 1978;Binder and Popp 1980) have been reported; as well as biotransformations for olivetol (McClanahan and Robertson 1984). However, the best studied biotransformations are in animals and humans (Mechoulam 1970;Watanabe et al 2007).…”
Section: Cannabinoid Biosynthesismentioning
confidence: 97%
“…It is well known that microorganisms such as fungi are capable to perform oxidation, reduction, isomerization reactions enzymatically, among other specific reactions. According to previous reports, Thamnidium elegans is used in biotransformations due to its allylic hydroxylase activity [28]. Also, it is known that bisabolol oxides may be vulnerable to allylic hydroxylation [29].…”
Section: Microbial Transformation and Analysis Of Metabolitesmentioning
confidence: 99%
“…The introduction of hydroxyl, carbonyl, carboxyl or glycosyl groups enhances the solubility of molecules in general. In 1980s, fungal and bacterial strains were already used to transform THC into polar derivatives (Binder and Meisenberg 1978 ; Binder and Popp 1980 ; Fukuda, Archer and Abbott 1977 ), as well as plant cell suspension cultures were used for the biotransformation of cannabinoids (Akhtar, Mustafa and Verpoorte 2015 ; Braemer and Paris 1987 ; Hartsel, Loh and Robertson 1983 ). Nevertheless, the overall yield of the metabolites was too low for pharmacological evaluation of the activity.…”
Section: Heterologous Systems For the Biosynthesis Of Cannabinoidsmentioning
confidence: 99%